Visual input to the mouse lateral posterior and posterior thalamic nuclei: photoreceptive origins and retinotopic order. (1st April 2016) - Allen, Annette E.; Procyk, Christopher A.; Howarth, Michael; Walmsley, Lauren; Brown, Timothy M.
Abstract : Key points: The lateral posterior and posterior thalamic nuclei have been implicated in aspects of visually guided behaviour and reflex responses to light, including those dependent on melanopsin photoreception. Here we investigated the extent and basic properties of visually evoked activity across the mouse lateral posterior and posterior thalamus. We show that a subset of retinal projections to these regions derive from melanopsin‐expressing retinal ganglion cells and find many cells that exhibit melanopsin‐dependent changes in firing. We also show that subsets of cells across these regions integrate signals from both eyes in various ways and that, within the lateral posterior thalamus, visual responses are retinotopically ordered. Abstract: In addition to the primary thalamocortical visual relay in the lateral geniculate nuclei, a number of other thalamic regions contribute to aspects of visual processing. Thus, the lateral posterior thalamic nuclei (LP/pulvinar) appear important for various functions including determining visual saliency, visually guided behaviours and, alongside dorsal portions of the posterior thalamic nuclei (Po), multisensory processing of information related to aversive stimuli. However, despite the growing importance of mice as a model for understanding visual system organisation, at present we know very little about the basic visual response properties of cells in the mouse LP or Po. Prompted by earlier suggestions that melanopsin photoreception might be important for certain functions of these nuclei, we first employ specific viral tracing to show that a subset of retinal projections to the LP derive from melanopsin‐expressing retinal ganglion cells. We next use multielectrode electrophysiology to demonstrate that LP and dorsal Po cells exhibit a variety of responses to simple visual stimuli including two distinct classes that express melanopsin‐dependent changes in firing (together comprising ∼25% of neurons we recorded). We also show that subgroups of LP/Po cells integrate signals from both eyes in various ways and that, within the LP, visual responses are retinotopically ordered. Together our data reveal a diverse population of visually responsive neurons across the LP and dorsal Po whose properties align with some of the established functions of these nuclei and suggest new possible routes through which melanopsin photoreception could contribute to reflex light responses and/or higher order visual processing. Key points: The lateral posterior and posterior thalamic nuclei have been implicated in aspects of visually guided behaviour and reflex responses to light, including those dependent on melanopsin photoreception. Here we investigated the extent and basic properties of visually evoked activity across the mouse lateral posterior and posterior thalamus. We show that a subset of retinal projections to these regions derive from melanopsin‐expressing retinal ganglion cells and find many cells that exhibit melanopsin‐dependent changes in firing. We also show that subsets of cells across these regions integrate signals from both eyes in various ways and that, within the lateral posterior thalamus, visual responses are retinotopically ordered.